(untitled) (Research, Society and Development, 2022)
Biosurfactants are amphipathic molecules with growing worldwide interest because of their low toxicity, high biodegradability and good ecological acceptability. They are produced by microorganisms and between them, filamentous fungi belonging Mucorales order have been reported as promising producers. However, most of these studies still use traditional submerged fermentation, a methodology with technical and economic problems. In this context, this work aimed the production of biosurfactant by Mucor hiemalis UCP 1309 using solid-state fermentation (SSF) as a low-cost alternative technology. Experiments were carried out using seven agro-industrial byproducts and wastes as substrates, supplemented with salt solution containing 5% waste soybean oil (WSO). Medium with the best result in the production of biosurfactant was used in a second fermentation, where a 22 full-factorial design (FFD) was performed to investigate the influence of inoculum size and concentration of WSO on surface tension. The results showed higher reduction of surface tension (to 28.1 mN/m) in fermentation using wheat bran. Also, the statistical analysis demonstrated significant effect of concentration of WSO on surface tension. Produced biosurfactant demonstrated excellent emulsifying properties with WSO, motor oil and burned motor oil, and the emulsions remained stable after 90 days of incubation. Therefore, this work demonstrated SSF as a suitable strategy for getting inexpensive and efficient biosurfactant and expediting its large-scale production. Moreover, we report, for the first time in the international literature, the production of biosurfactant using SSF by a Mucoralean fungus.